Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1186/s12890-021-01723-z
|View full text |Cite
|
Sign up to set email alerts
|

High-throughput next-generation sequencing for identifying pathogens during early-stage post-lung transplantation

Abstract: Background High-throughput next-generation sequencing (HT-NGS) has the potential to detect a large variety of pathogens; however, the application of HT-NGS in lung transplant (LTx) recipients remains limited. We aimed to evaluate the value of HT-NGS for pathogen detection and diagnosis of pulmonary infection during early-stage post-lung transplantation. Methods In this retrospective study, we enrolled 51 LTx recipients who underwent lung transplant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 42 publications
0
10
0
Order By: Relevance
“…Additionally, DSA should be present for AMR. Pulmonary infection was diagnosed based on our previous studies [27,28]. There were no pathogens in the AR or CLAD groups.…”
Section: Histopathology From Lung Biopsy Tissuementioning
confidence: 99%
“…Additionally, DSA should be present for AMR. Pulmonary infection was diagnosed based on our previous studies [27,28]. There were no pathogens in the AR or CLAD groups.…”
Section: Histopathology From Lung Biopsy Tissuementioning
confidence: 99%
“…was associated with reduced lung function [ 69 ]. When it comes to early symptomatic pulmonary infection after lung transplantation, NGS was superior to traditional pathogen detection (88.24% vs. 76.47%) [ 70 ]. In patients who underwent hematopoietic cell transplantation with pneumonia, cell-free plasma DNA sequencing (cfDNA-seq) detected infections involving more than a single pathogenic mold (especially non- Aspergillus species) in 38 of the 75 patients [ 71 ].…”
Section: Ngs and Fungal Infection In Different Organsmentioning
confidence: 99%
“…Among the fteen included studies, the highest positive likelihood ratio is found in Jiang J's study, whose value is 24.34 (95%CI, 10.73-55. 21). The lowest positive likelihood ratio occurs in the Pan T study with a value of 1.50 (95%CI, 0.57-39.95).…”
Section: Sensitivity Speci City Plr Nlr Diagnostic or And Sroc Curvementioning
confidence: 99%